Occurrence of occupational accidents in a teaching clinic in the state of São Paulo: a retrospective study (Research, Society and Development, 2022)
Percutaneous lesions with biological material are frequent in the dental clinic and are risk factors associated with communicable diseases. However, it is believed that knowledge about prevention and the care that must be implemented comes from professional training. Thus, the aim of this study was to evaluate the occurrence of needlestick injuries in a dental school clinic and to propose measures to prevent and control the occurrence of perforations. This is a retrospective study carried out by consulting notification sheets of needlestick injuries evaluated over a period of ten years in the dentistry course of the University Center of the Fundação Educacional de Barretos. The collected data were analyzed using Excel® software and expressed through descriptive statistics, in relative frequencies. Thus, 2952 students were analyzed, with 3% of notification, emphasis on females (72.5%), in the third year of graduation (68.8%) with greater frequency in the discipline of integrated clinic (47.5%). Despite the absence of a detailed description, 69% of the accident cases were caused by a sharp instrument. The occurrence of needlestick accidents is significant and changes in the methods of notification and guidance to students are necessary in order to facilitate communication between the educational institution, government agencies and undergraduates.